Analisis Al-Iqtibas pada Ayat Al-Qur’an dan Hadist - Lisa Rahmadhani Siregar; Adil Rambe; Mutia Syahdina; Harun Al-Rasyid (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
his study aims to analyze the concept of al-iqtibas in verses of the Qur'an and Hadith. Al-iqtibas is a technique of quoting or borrowing parts of texts found in the Qur'an and Hadith in various contexts, both in literature and speeches. This research employs a descriptive qualitative approach with textual analysis methods to understand how al-iqtibas is utilized in both classical and contemporary Islamic traditions. The findings show that al-iqtibas plays an essential role in strengthening religious arguments and enhancing the aesthetic value of texts, while also serving as an effective medium for conveying moral and spiritual messages. Furthermore, the study finds that the use of al-iqtibas is not limited to religious contexts but also extends to cultural and social realms. This research is expected to enrich the understanding of intertextuality in the study of the Qur'an and Hadith and contribute to the development of Islamic linguistic studies.